2018
DOI: 10.1016/j.drugpo.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related police encounters across the globe: How do they compare?

Abstract: The findings unearth significant cross-national differences in the incidence and nature of drug-related policing of people who use drugs. This suggests that there may be opportunities for countries to learn from each other about how and why they differ, and the potential benefits of switching to lower intensity modes of drug policing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…This is supported by a public health approach to drug use in the Netherlands more generally. Drug policy is the preserve of the Ministry of Health, with prosecutions for possession of drugs relatively rare [15,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a public health approach to drug use in the Netherlands more generally. Drug policy is the preserve of the Ministry of Health, with prosecutions for possession of drugs relatively rare [15,42].…”
Section: Discussionmentioning
confidence: 99%
“…Policing practices in relation to DCS in Scotland are a key factor which could either facilitate engagement, through publichealth aligned practice, or act as a barrier to engagement, through enactment of the enforcement-based practices outlined above. Given strong evidence that criminalisation of personal possession is contrary to harm reduction and public health goals [27,30,[40][41][42][43], shifting practice towards a more public health-based approach holds promise for addressing the current high levels of drug related harms in Scotland, through enabling access to harm reduction services such as DCS.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of policing for drug use among particular populations is well documented [ 34 , 35 ]. In Australia, studies on social bias in policing have found higher rates of stop and search and arrests for drug use for people who are younger, male, Aboriginal, a minority ethnicity, unemployed and with prior police encounters [ 36 , 37 , 38 ]. Further research with both the police and disadvantaged populations is therefore warranted to better understand the scale of negative policing regarding the ACT cannabis bill, the experiences of disadvantaged populations with cannabis law reform, and other implementation challenges.…”
Section: Discussionmentioning
confidence: 99%
“…One such group of working dogs is Drug Detection Dogs (DDDs); dogs that have been trained to search and identify various target odours, including narcotics or other drugs, on command. A crossnational analysis involving 26 countries revealed Australia as one of the top 4 countries (along with Italy, Scotland and the UK) for high frequency use of DDDs, up to 14 times more common than some other countries when controlling for individual and national factors (Hughes et al, 2018). In Australia, these dogs can be found in government agencies such as Australian Border Force (formerly Customs), Australian Federal Police, State and Territory Police, and Correctional Services.…”
Section: Introductionmentioning
confidence: 99%